(untitled) - Theron, Johannes Stephanus

The effect of crop rotation and tillage practices on Fusarium crown rot of wheat, agronomic parameters of wheat production and residue decomposition in the Western Cape of South Africa (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.